Beliefs about benefits and harms of medications and supplements for brain health - Zachary A. Marcum; Sarah D. Hohl; Douglas Barthold; Oleg Zaslavsky; Eric B. Larson; Shelly L. Gray (Preventive Medicine Reports, 2020)
The role of medications and supplements for brain health is a fast-changing and growing field, making it difficult for patients to receive updated and accurate information. The objective of this study was to assess patients’ beliefs about the helpfulness or harmfulness of various medications and supplements on brain health. A convenience sample of adults from an integrated healthcare system completed a web-based survey. Descriptive statistics were used for this hypothesis-generating study. A total of 1661 respondents completed the survey. The majority of respondents were female (77%), between the ages of 51–70 (64%), and white (89%). Across the selected medications and supplements purported to improve a person’s brain health (vitamin E, ginkgo biloba, hormones such as estrogen or testosterone, fish oil, and statins), 46–64% of respondents reported not knowing or skipped the item regarding their helpfulness to improve brain health. One out of four respondents reported benefits of vitamin E and nearly half reported benefits of fish oil on brain health; neither benefit is supported by current evidence. For the two medication classes evaluated for increasing dementia risk (proton pump inhibitors and anticholinergics used as sleep aids), 63–77% of respondents reported not knowing or skipped the item regarding their harmfulness to brain health. Survey respondents largely reported not knowing the potential benefits and harms of different medications and supplements for brain health. Improved health communication on pharmaceutical effects on dementia risk is greatly needed, and its development and dissemination should involve healthcare providers, patients, and media outlets. Keywords: Dementia, Alzheimer’s disease, Supplements